Konstanta Salat Jamak 12 RMA dalam Matematika 472319 Hahslm di Era Ekonomi Covid - R Mochamad A (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this study is to analyze the combination of four-digit numbers that relate to the Plural Prayer Constant of 12 RMA in Hahslm 472319. This research was conducted by literature studies from electronic media, books, journals, and other data sources. The methodology used constructive quantitative that refers to Quran with the equation of 47319 in Hahslm. The research results are combination numbers of four-digit by subtracting the decreasing left phrase to the increasing right phrase that will reach the number 6174 at the maximum of the seventh step. Mathematically, this sequence number has the same as the Plural Prayer Constants of 12 RMA and has a similarity to the 472319 formula. This 12 RMA constant is stored in the plural prayers 1 (Fajr) and 2 (Dhuhur Asr and Maghrib Isa). The number 19 is also encrypted in Covid which influences the economic crisis.